Manuscript Books: Collections of Political Life Materials from the Area of the Grand Duchy of Lithuania Dating Back to the 17th and 18th Centuries in Libraries, Archives and Museums in Poland - Matwijów, Maciej (Knygotyra, 2021)
The article discusses manuscript books – collections of public life materials created in the 17th and 18th centuries in the Grand Duchy of Lithuania, now located in Poland. They were created mainly by nobles and by chancellery clerks and officials employed at magnates’ and state dignitaries’ courts as an expression of the interests of collectors or documentary and historiographical concerns, and sometimes also as support for public activity. They contained various materials related to conducting, documenting and recording public life. The present overview is based on an identification of copies and on the information contained in printed and online manuscript catalogues and inventories. The number of surviving manuscripts of that type can be hypothetically estimated at ca. 400–500 copies, with ca. 100 copies identified in Poland. Their largest collection is held in the Radvilos Archives, part of the Central Archives of Historical Records in Warsaw, with single copies scattered across different libraries and museums. The oldest ones date back to the late 16th and early 17th centuries. The greatest value should be attributed to several manuscripts originating from the Radvilos of Biržai community from the mid-17th century. Other valuable manuscripts include some made by common nobles, especially in the 17th century, as they often contain unique materials, unknown from elsewhere, as well as those created in the circles of the Sapiegos and Radvilos of Nyasvizh magnate families. Standing out among the latter are miscellanies created during the first three decades of the 18th century by Kazimierz Złotkowski, secretary of the Grand Chancellor of Lithuania Karolis Stanislovas Radvila. These books attest to the integration of the Grand Duchy of Lithuania’s nobility and magnates with other lands of the Polish-Lithuanian Commonwealth. They largely contain materials relating to public life of the whole Commonwealth, while often including materials relating to local issues.